Multimetal organic frameworks as drug carriers: Aceclofenac as a drug candidate - Al Haydar, Muder; Abid, H.; Sunderland, B.; Wang, Shaobin (Dove Medical Press Ltd., 2019)
Background: Multimetal organic frameworks (M-MOFs) were synthesized by including a second metal ion with the main base metal in the synthesis process to enhance their applications for drug delivery. Aceclofenac (ACF), a nonsteroidal anti-inflammatory analgesic drug of low aqueous solubility, was selected as a candidate for the drug delivery system Purpose: This study aimed to evaluate the loading capacity (LC) and entrapment efficiency (EE) percentages of multi-Material of Institute Lavoisier (MIL)-100(Fe) (M-MIL-100(Fe)) for ACF. Materials and methods: Hydrothermal synthesis procedure was used to prepare multi-MIL-100(Fe) samples (Zn I-MIL-100(Fe), Zn II-MIL-100(Fe), Ca I-MIL-100(Fe), Ca II-MIL-100-(Fe), Mg I-MIL-100(Fe), Mg II-MIL-100(Fe), Mn I-MIL-100(Fe), and Mn II-MIL-100(Fe)). The characterization of M-MIL-100(Fe) samples was evaluated by X-ray powder diffraction (XRD), Fourier transform infrared spectra, scanning electron microscope (SEM), TGA, and N2 adsorption isotherms. The LC of M-MIL-100(Fe) and EE of ACF were determined. Nuclear magnetic resonance (NMR) and zeta-potential analyses were employed to confirm qualitatively the drug loading within M-MIL-100(Fe). Results: The ACF LC of MIL-100(Fe) was 27%, whereas the LC of M-MIL-100(Fe) was significantly increased and ranged from 37% in Ca I-MIL-100(Fe) to about 57% and 59% in Mn II-MIL-100(Fe) and Zn II-MIL-100(Fe), respectively. The ACF@M-MOFs release profiles showed slow release rates in phosphate buffer solutions at pH 6.8 and 7.4 as compared to the ACF@MIL-100(Fe). Conclusion: Therefore, M-MOFs showed a significant potential as a carrier for drug delivery systems.